2009
DOI: 10.1111/j.1365-2362.2009.02212.x
|View full text |Cite
|
Sign up to set email alerts
|

High plasma levels of the soluble receptor for advanced glycation endproducts in patients with symptomatic carotid atherosclerosis

Abstract: Plasma levels of sRAGE are higher in symptomatic than asymptomatic carotid atherosclerosis. Higher levels of sRAGE in symptomatic patients may be markers of a higher degree of vascular inflammation in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…Here, we expand these explorations to the relationships between sRAGE and carotid IMT and plaque. Prior studies have demonstrated a relationship between total sRAGE or esRAGE and carotid IMT (10;21), but very limited data exists between sRAGE levels and carotid plaque (22). In the current study we did not see any relationship with carotid IMT or plaque presence.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we expand these explorations to the relationships between sRAGE and carotid IMT and plaque. Prior studies have demonstrated a relationship between total sRAGE or esRAGE and carotid IMT (10;21), but very limited data exists between sRAGE levels and carotid plaque (22). In the current study we did not see any relationship with carotid IMT or plaque presence.…”
Section: Discussionmentioning
confidence: 99%
“…One is that high plasma glucose may heighten blood viscosity and quicken the conduction of PWV [9]. Another is that high plasma glucose can quicken the course of atherosclerosis because high plasma can raise the content of advanced glycation endproducts [10].…”
Section: Univariate Correlation Between Bapwv and Selected Clinical Vmentioning
confidence: 99%
“…Plasma CML and sRAGE levels were elevated after percutaneous coronary interventions with stenting, and positively associated with the extent of vascular injury (80). Further, Basta et al reported that plasma sRAGE levels were higher in non-diabetic patients with symptomatic carotid atherosclerosis than those without symptom (81). They also showed that in symptomatic patients, plasma levels of sRAGE were positively associated with CML, and CML and RAGE levels in carotid plaques were correlated with each other (81).…”
Section: Srage and Cvdmentioning
confidence: 99%